2015
DOI: 10.18632/oncotarget.4451
|View full text |Cite
|
Sign up to set email alerts
|

USP35 activated by miR let-7a inhibits cell proliferation and NF-κB activation through stabilization of ABIN-2

Abstract: Ubiquitin specific protease 35 (USP35) is a member of deubiquitylases (DUBs). It remains largely unknown about the biological role and the regulation mechanism of USP35. Here, we first identified miR let-7a as a positive regulator of USP35 expression and showed that USP35 expression positively correlates with miR let-7a expression in different cancer cell lines and tissues. Then, we showed that USP35 expression was decreased dramatically in the tumor tissues compared with the adjacent non-cancerous tissues. US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 40 publications
0
35
1
Order By: Relevance
“…More and more reports showed that miRNAs play an important role in regulating various biological behaviours, including cancer cell survival, apoptosis, oxygen stress, and maintenance of cell phenotype [6, 8, 10]. Altered expression of miRNAs is usually related to different kinds and types of tumors, sunch as breast cancer, gliomas, and liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…More and more reports showed that miRNAs play an important role in regulating various biological behaviours, including cancer cell survival, apoptosis, oxygen stress, and maintenance of cell phenotype [6, 8, 10]. Altered expression of miRNAs is usually related to different kinds and types of tumors, sunch as breast cancer, gliomas, and liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Although NF-κβ signaling has not been studied in the context of scleral remodeling and myopia, regulation of type I collagen is directly relevant because it is the main component of the scleral matrix, and myopic scleras show reduced collagen levels. 41 Other members of the Let-7 family also showed differential expression in our study, including Let-7b, previously shown to be involved in COL1A1 and COL1A2 regulation in skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Data provided by Zhang et al indicated that overexpression of USP28 in lung cancer and silencing of USP28 expression in A549 lung cancer cells inhibited cell proliferation and induced apoptosis. In contrast, Liu et al found that USP35 was downregulated in breast and lung cancer. Ectopic expression of USP35 in H1299 lung cancer cells inhibited cell proliferation.…”
Section: Introductionmentioning
confidence: 86%